Gold nanoparticles synthesized by laser ablation in deionized water - Al-Azawi, Mohammed A. (Physical Society of the Republic of China, 2015)
Gold nanoparticles were prepared by the pulsed laser ablation of high purity gold bulk immersed in deionised water. Pulses of a Q-switched Nd:YAG laser (fundamental wavelength, 1064 nm; laser fluence, 15 J/cm2; pulse duration, 8 ns) were employed to irradiate the gold surface during the ablation process. The effects of the thickness of the liquid layer and the post-ablative modification processes on ablation efficiency, size, and aggregation of gold nanoparticles were investigated. The experimental conditions that yielded the maximum ablation efficiency were determined. The average size and redistribution of nanoparticles were controlled by the subsequent treatment of the ablated colloid solution with a combination of 1064 and 532 nm pulses. The effects of post-ablation under laser-induced nanoparticles modification reduced the average particle size from 15.12 nm to 9.5 nm; the size distribution was also narrowed with 532 nm pulses. The results of UV-Vis spectrophotometer and transmission electron microscopy were exploited to characterize the optical spectra of gold colloidal solutions as well as to analyze the final shape and particle size distribution, respectively